Mathematical literacy for slow learners: a review of access and quality of elementary school education - Herjan Haryadi; Woro Sri Hastuti; Trisna Kusuma Wardani; Ruhil Ismafitri (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
The 2030 Sustainable Development Goals (SDGs) on inclusive and equitable quality education have elevated inclusive education to a high priority in a global context. Mathematical literacy is not simply the ability to calculate, but a fundamental competency for individuals to fully participate in a modern, data-driven society. This study aims to analyse the equity and quality of the mathematical literacy learning process for slow-learning students. The research method used is qualitative. The type of research is phenomenological. The qualitative research design consists of three stages: orientation, focused exploration, and data analysis. Data collection techniques include interviews, observation, and documentation. The data analysis technique used is Miles and Huberman's data analysis, which is a systematic and interactive method for analysing qualitative data. The results of this study indicate that schools and curricula are not flexible enough to address the unique needs of each slow-learning student in learning mathematical literacy. This includes modifying the curriculum and learning strategies to suit their individual potential. Schools have not fully provided physical access or safe facilities for slow-learning students. Students tend to adapt to school. Assessments given to slow-learning students in summative assessments tend to be similar to those given to non-slow-learning students. Inhibiting factors include the lack of teacher competency development in assisting slow-learning students and limited facilities and teaching material for slow-learning students.